LEGAL RESPONSIBILITY OF SKIZOFRENIA PATIENTS AS A CRIMINAL PREPETRATOR - Aisy, Bilqis Rihadatul; Ibrahim, Dina Oktarina; Haruna Intang, Khusnul Katimah; Tindage, Monique Anastasia (Tadulako Law Review, 2019)
The study, entitled Liability Law of People with Schizophrenia as an Actor Crime aims, first to analyze ability schizophrenic responsible under criminal law. Second, to know the reasons for the criminal punishment for a schizophrenic who committed a criminal act. The method used in this paper is a normative legal research method which is the legal research literature that examines the methods used in the existing library materials using the approach of legislation (Statue Approach). Concluded based on the results of this study, first: the person be able bear the responsibility under the criminal law seen from the ability irresponsibility, while schizophrenic who has a disorder that is psychosis or illness on the ability of common sense (ziekelijke storing) does not have the ability to be responsible as the condition is made clear by article 44 paragraph (1) Criminal Code which explains that people with disabilities in the growth of his soul (gebrekkige ontwikkeling) or impaired due to illness (ziekelijke storing) can not be held accountable and can not be convicted. Second: skizophrenia patients who commits an offense is punishable with some legal considerations that there is evidence in the form of post mortem, the fulfillment of the elements and their causal relationship deeds and psychiatric conditions.